Supplementation-induced change in muscle carnosine is paralleled by changes in muscle metabolism, protein glycation and reactive carbonyl species sequestering - Schön, M; Just, I; Krumpolec, P; Blažíček, P; Valkovič, L; Aldini, G; Tsai, C-L; De Courten, B; Krššák, M; Ukropcová, B; Ukropec, J (Physiological research, 2023)
Carnosine is a performance-enhancing food supplement with a potential to modulate muscle energy metabolism and toxic metabolites disposal. In this study we explored interrelations between carnosine supplementation (2 g/day, 12 weeks) induced effects on carnosine muscle loading and parallel changes in (i) muscle energy metabolism, (ii) serum albumin glycation and (iii) reactive carbonyl species sequestering in twelve (M/F=10/2) sedentary, overweight-to-obese (BMI: 30.0+/-2.7 kg/m2) adults (40.1+/-6.2 years). Muscle carnosine concentration (Proton Magnetic Resonance Spectroscopy; 1H-MRS), dynamics of muscle energy metabolism (Phosphorus Magnetic Resonance Spectroscopy; 31P-MRS), body composition (Magnetic Resonance Imaging; MRI), resting energy expenditure (indirect calorimetry), glucose tolerance (oGTT), habitual physical activity (accelerometers), serum carnosine and carnosinase-1 content/activity (ELISA), albumin glycation, urinary carnosine and carnosine-propanal concentration (mass spectrometry) were measured. Supplementation-induced increase in muscle carnosine was paralleled by improved dynamics of muscle post-exercise phosphocreatine recovery, decreased serum albumin glycation and enhanced urinary carnosine-propanal excretion (all p<0.05). Magnitude of supplementation-induced muscle carnosine accumulation was higher in individuals with lower baseline muscle carnosine, who had lower BMI, higher physical activity level, lower resting intramuscular pH, but similar muscle mass and dietary protein preference. Level of supplementation-induced increase in muscle carnosine correlated with reduction of protein glycation, increase in reactive carbonyl species sequestering, and acceleration of muscle post-exercise phosphocreatine recovery.
Keywords: Muscle, Skeletal; dospělí; kosterní svaly; Dietary Supplements; Maillardova reakce; karnosin; lidé; Carnosine; Maillard Reaction; fosfokreatin; Phosphocreatine; potravní doplňky; Adult; Humans